2014
DOI: 10.1097/aog.0000000000000104
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hemodynamics by Thoracic Impedance Cardiography for Normal Pregnancy and the Postpartum Period

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
2
12
1
Order By: Relevance
“…Our LVOT VTI , HR, SV and CO values were comparable to published echocardiography values in similar gestation women [ 19 , 20 ]. ICG-derived mean values for SV and CO in the current paper were also comparable to those previously published in similar gestation women [ 21 ]. At 6.5 ± 2.5%, the echocardiography CoV in the current study is lower than previously reported 8.8% for cardiac output [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Our LVOT VTI , HR, SV and CO values were comparable to published echocardiography values in similar gestation women [ 19 , 20 ]. ICG-derived mean values for SV and CO in the current paper were also comparable to those previously published in similar gestation women [ 21 ]. At 6.5 ± 2.5%, the echocardiography CoV in the current study is lower than previously reported 8.8% for cardiac output [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Compared with echocardiography, ICG is able directly to evaluate myocardial pump function, SV and thoracic fluid content, and changes can be measured instantaneously and monitored continuously. Using ICG, previous studies confirmed that CO increased from the first trimester, peaked by the end of the second trimester and then slightly decreased in the third trimester . Given the concomitant opposite changes in MAP, with a nadir at 20 weeks, SVR decreased in the first half of the pregnancy and then increased until the end of the third trimester.…”
Section: Discussionmentioning
confidence: 82%
“…The process involves spiral artery luminal obliteration due to phenomena such as thrombosis, endarteritis and intima thickening 14 , which result in increased local vascular resistance 15 . Although this finding may reflect systemic circulatory changes 16 17 , an immediate cause for the events is the mechanical pressure imposed by the contracted postpartum myometrium, as well as, possibly, local immunological phenomena 18 . As the structural involution of the uterine artery and distal branches occurs, functional changes can be assessed using a computerised analysis of the blood velocity spectrum obtained with Doppler ultrasound.…”
Section: Discussionmentioning
confidence: 95%